Genomic Analysis of a New Serovar of Leptospira weilii Serogroup Manhao - Xu, Yinghua; Zheng, Huajun; Zhang, Ying; Wang, Yuezhu; Zhang, Jinlong; Li, Zhe; Cui, Shenghui; Xin, Xiaofang; Ye, Qiang; Chang, Yung-Fu; Wang, Junzhi (Frontiers in Microbiology, 2017)
Leptospirosis, caused by pathogenic Leptospira spp., is recognized as an important emerging zoonotic disease throughout the world. In this study, multiple approaches were used to characterize the recently discovered serovar Heyan strain L231. This strain can infect guinea pigs and belonged to the pathogenic species L. weilii. Genome sequencing analysis revealed the draft genome of 4.2 M bp with a G+C content of 40.67% for strain L231, and a total of 4,794 ORFs were identified. The strain L231 genome was found to have a larger LPS biosynthesis locus than that of strains L. interrogans serovar Lai and L. borgpetersenii serovar Hardjobovis. Phylogenomic reconstructions showed that the evolutionary position of L. weilii serovar Heyan was different from that of other serovars from serogroup Manhao. These findings may lead us to a better understanding of Leptospira pathogenesis and evolution.